2014
DOI: 10.1103/physrevb.90.054304
|View full text |Cite
|
Sign up to set email alerts
|

Preserving entanglement and nonlocality in solid-state qubits by dynamical decoupling

Abstract: In this paper, we study how to preserve entanglement and nonlocality under dephasing produced by classical noise with large low-frequency components, such as 1/f noise, using dynamical decoupling techniques. We first show that quantifiers of entanglement and nonlocality satisfy a closed relation valid for two independent qubits locally coupled to a generic environment under pure dephasing and starting from a general class of initial states. This result allows us to assess the efficiency of pulse-based dynamica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 88 publications
1
78
0
Order By: Relevance
“…The use of either DD techniques or non-Markovian effects prolongs the preservation of both entanglement and discord in presence of environmental noise [31][32][33][34][35]. However, studies of single qubit dynamics have recently shown that the simultaneous use of non-Markovian reservoir engineering and DD protocols is counterproductive for coherence preservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of either DD techniques or non-Markovian effects prolongs the preservation of both entanglement and discord in presence of environmental noise [31][32][33][34][35]. However, studies of single qubit dynamics have recently shown that the simultaneous use of non-Markovian reservoir engineering and DD protocols is counterproductive for coherence preservation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, two all-optical experiments have already confirmed that quantum entanglement can either spontaneously revive [22] or be recovered by local operations [31] in non-Markovian classical environments. Few tentative explanations have been provided so far: one relies on the role played by the classical environment as a control mechanism which, thanks to the memory effect, keeps a record for what operation has been applied to the quantum system [21,22]; another one is based on the concept of hidden entanglement, that is, the amount of quantum correlations not revealed by the density matrix description of the system state that can surface by means of local operations [30,31,36].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to PDD, the gate error under CP is weakly dependent on γ M (the quasi-static approximation is valid until γ M ≤ . On the other side, the gate performance under UDD is the very sensitive to the high-frequency (soft) cut-off of the noise, analogously to other analysis 23,66 .…”
Section: Carr-purcell and Uhrig Dynamical Decouplingmentioning
confidence: 99%
“…Recently, the lifetime of an entangled state of a superconducting flux qubit coupled to a microscopic two-level fluctuator has been enhanced by DD techniques 52 . Entanglement preservation between independent qubits (storage) from local pure dephasing random-telegraph and 1/f noise by dynamical decoupling has been predicted 53,54 and demonstrated in an all-optical experiment 55 .…”
Section: Introductionmentioning
confidence: 99%